A reconstruction of authentic performance in selected organ works of Cesar Franck from historical sources and recorded performances - Edgecombe, Colleen Jane (My University, 1995)
This study is an investigation of the performance practice observed by organists when recording the organ works of Cesar FrancK against the criteria of score, instrument and tradition. Based on these findings, a more informed reconstruction of the interpretations and manners of performance employed by the composer and his contemporaries is obtained. [Abbreviated Abstract. Open document to view full version]
A Dissertation submitted for the Degree of Master of Music to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 1995
Keywords: Franck, César,--1822-1890 .; Organ music.